Impact Accelerations of Barefoot and Shod Running - Thompson, M.; Seegmiller, J.; McGowan, C. P. (International Journal of Sports Medicine, 2016)
During the ground contact phase of running, the body’s mass is rapidly decelerated resulting in forces that propagate through the musculoskeletal system. The repetitive attenuation of these impact forces is thought to contribute to overuse injuries. Modern running shoes are designed to reduce impact forces, with the goal to minimize running related overuse injuries. Additionally, the fore/mid foot strike pattern that is adopted by most individuals when running barefoot may reduce impact force transmission. The aim of the present study was to compare the effects of the barefoot running form (fore/mid foot strike & decreased stride length) and running shoes on running kinetics and impact accelerations. 10 healthy, physically active, heel strike runners ran in 3 conditions: shod, barefoot and barefoot while heel striking, during which 3-dimensional motion analysis, ground reaction force and accelerometer data were collected. Shod running was associated with increased ground reaction force and impact peak magnitudes, but decreased impact accelerations, suggesting that the midsole of running shoes helps to attenuate impact forces. Barefoot running exhibited a similar decrease in impact accelerations, as well as decreased impact peak magnitude, which appears to be due to a decrease in stride length and/or a more plantarflexed position at ground contact.
Keywords: biomechanics; locomotion; heel strike; running; footstrike; impact